Experimental Capitalism : A study of Design for ‘Future Digital Manners’ - Lange, Ann-Christina (STS Encounters, 2016)
From the introduction: The question of how aesthetic practices create economic value is a question of the way in which specific artistic and critical practices feed into a capitalistic order of production. In this paper I draw attention to this question within the practice of Critical Design. I study a 4-week design brief that took place at the Royal College of Art in London 2009. More generally, I account for the inclusion of artistic tools in the process of invention as a response to a capitalistic logic of order, where economic value are dependent on the valorisation of affective labour and provocative means of invention. This exploration aims to contribute to a temporal-ontological approach to innovation following the definition by Sanford Kwinter saying that: ‘… no novelty appears without becoming and no becoming without novelty’ (Kwinter 2001 p. 5). From my participation in the brief I consider a specific artistic intervention called the Berlin Street experiment and the way in which the experience of that event co-constitute the experimental setting.